URGENSI KEBIJAKAN PENANAMAN MODAL NON FISKAL TERKAIT FASILITAS PELAYANAN TERPADU SATU PINTU (PTSP) DI BIDANG KEIMIGRASIAN DI INDONESIA - Ni Ketut Wiratny; Putu Eka Trisna Dewi (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2018)
Investment is any form of investment activities, either by domestic investors or foreign investors to do business in the territory of the Republic of Indonesia. In principle, investment is done without discrimination. The Government provides non-licensing services for investment, namely all forms of ease of fiscal services, and non-fiscal services as well as information on investment, in accordance with the provisions of legislation. Special non-fiscal services the government has issued a policy conducive to the acceleration of services. The policy is One Stop Integrated Service. This policy aims to assist investors in obtaining ease of services, fiscal facilities, and information on investment. One form of One Stop Integrated Service policy is the immigration facilities provided to foreign investors investing in Indonesia. It is expected that with this policy investment in Indonesia will increase and have a positive impact on the life of local people.